1986
DOI: 10.1200/jco.1986.4.2.244
|View full text |Cite
|
Sign up to set email alerts
|

Tumor heterogeneity and drug resistance.

Abstract: Drug resistance has long been identified as a major reason for therapy failure in cancer patients. Concurrently, work from many laboratories in the past 10 years has established tumor heterogeneity as a phenomenon of critical importance in the natural history of individual neoplasms. The two most sinister aspects of intraneoplastic diversity in human solid tumors are the genesis of clones with metastatic potential, and the existence of drug-resistant variants in primary cancers and their metastases. Thus, rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
101
0
1

Year Published

1989
1989
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(106 citation statements)
references
References 78 publications
2
101
0
1
Order By: Relevance
“…It was found that with increasing DOX resistance the population composition gradually changes from a population in which most cells contain three Topolla gene copies to a population in which most cells contain only two copies. This change is in agreement with the hypothesis that during resistance development in human tumours, the resistant cells are initially sporadically present in a genetically heterogeneous tumour, and selected by drug exposure (Dexter and Leith, 1986 (Keith et al, 1993;Murphy et al, 1995). Thus other genes on the same chromosome might be essential for the selection procedure as well.…”
Section: Discussionsupporting
confidence: 78%
“…It was found that with increasing DOX resistance the population composition gradually changes from a population in which most cells contain three Topolla gene copies to a population in which most cells contain only two copies. This change is in agreement with the hypothesis that during resistance development in human tumours, the resistant cells are initially sporadically present in a genetically heterogeneous tumour, and selected by drug exposure (Dexter and Leith, 1986 (Keith et al, 1993;Murphy et al, 1995). Thus other genes on the same chromosome might be essential for the selection procedure as well.…”
Section: Discussionsupporting
confidence: 78%
“…The clinical and pharmacological use of combination chemotherapy has been widely studied in animal models (Dexter et al, 1986). The combination of antineoplastic drugs has several advantages over single drug treatment: (1) increasing therapeutic synergism by exploiting different mechanisms of action; (2) increasing patient tolerance by minimizing side-effects of drugs owing to lower doses of each individual compound; and (3) preventing or delaying the emergence of resistant cell clones.…”
Section: Discussionmentioning
confidence: 99%
“…It has long been recognized that tumors are heterogeneous and comprise multiple subpopulations that likely provide a survival and growth advantage for primary tumors and their metastases (65)(66)(67)(68). Tumor cell heterogeneity confounds our understanding of tumor progression, relapse, and therapy (3,7,69).…”
Section: Discussionmentioning
confidence: 99%